Fluidized bed gasification of biomass from plant assisted bioremediation (PABR): Lab-scale assessment of the effect of different catalytic bed material on emissions. (15th August 2022) - Gallucci, F.; Palma, A.; Vincenti, B.; Carnevale, M.; Paris, E.; Ancona, V.; Migliarese Caputi, M.V.; Borello, D.
Highlights: Biomass from contaminated soils to renewable energy production. Study for the choice of the most performing material for a fluidized bed gasifier. The metals release from bed materials was never properly assessed up to now. Study of TGA – ICP/MS method to predict the syngas contamination from heavy metals. Abstract: The interaction between biomass from plant assisted bioremediation processes PABR contaminated with heavy metals and the bed materials used in Fluidized Bed Gasifier FBG systems was experimentally studied to identify the origin of the metals detected in syngas and/or solid residues, and affecting the quality of the produced fuels and biochar. The characteristics of an arboreal (poplar pruning) and an herbaceous biomass (Arundo Donax), both previously used in phytoremediation processes, were evaluated. The bed materials have been identified among those most used in pyrogasification processes, such as olivine, K-feldspar, kaolinite and calcite. The simulation of the process and the sampling of the syngas was carried out by means of an instrumental apparatus composed of TGA-DSC connected with a system of bubblers for the capture of heavy metals HM. The analysis of the matrices and the bubbled solutions in ICP-MS allowed to experimentally evaluate quantity and composition of HM released. The analyses showed that calcite gives the best results for both arboreal and herbaceous biomass but it has the disadvantage of losing about 55 % in weight during the process, releasing CO and CO2 and becoming CaO. The criteria for choosing the most suitable material for the bed of an arboreal or herbaceous biomass gasification were carried out mainly on the basis of the heavy metals released during the process. The study provides useful results for the assessment of the bed materials in FBG conversion process using PABR biomass. From a comparison between all the parameters considered and the Principal Component Analysis (PCA) results, it emerges that K-feldspar represent the best optimization for the materials that can be used in FBG beds both in the case of arboreal and herbaceous plants, while olivine is particularly effective only with arboreal biomass.